Law, Custom, and Statute in the Muslim World : Studies in Honor of Aharon Layish - Layish, Aharon, 1933-2022; Shaham, Ron (Studies in Islamic law and society ;, 2007)
Deals with the main components in the laws of Islamic societies, past and present: shari'a custom, and statute. This book includes chapters that focus on one of these components, and that discuss the interplay between two or even all three of them. It offers a wide geographical coverage, from the Balkans to Yemen, and from Iraq to the Maghrib.